Geoffrey Groundhog predicts the weather - Koscielniak, Bruce (Houghton Mifflin, 1995)
When Geoffrey Groundhog pops out of his hole to predict the weather, he is blinded by television cameras and lights and is unable to see if he has a shadow. No one in town knows how to proceed, so Geoffrey needs help fast.